Remote home visits: Exploring the concept and applications of remote home visits within health and social care settings. (January 2022) - Jones, Natalie Louise; Read, Jennifer; Field, Becky; Fegan, Colette; Simpson, Emma; Revitt, Claire; Lanfranchi, Vita; Ciranvenga, Fabio
Introduction: This study consulted intended users and adopters of technology about a remote home visit application called Virtual Visit Approach. Participants were shown a video of a 'mock' remote home visit and asked to discuss the potential benefits, barriers and uses they could envisage. Methods: Purposive sampling brought together stakeholders, patients and public representatives to capture thoughts, feelings and views in co-design workshops. Primary qualitative data were collected in real time. Post workshop, they were analysed and categorised into key themes and subthemes. Findings: The opportunity to conduct remote home visits was regarded as a positive adjunct to usual practice. However, concerns about the quality of remote assessments were expressed by participants in the workshops. Conclusion: The NHS response to COVID-19 sparked a national roll out of the use of video conferencing technology. The opportunity to access technology to conduct remote visits and consultations, has instigated a seismic change in the way healthcare is delivered now and for the future. However, there is much we do not yet know about the impact on the intended adopters and users of remote visits and consultations. This study demonstrated the importance of involving intended adopters and users in the co-design of technology to explore potential benefits, barriers and uses providing valuable insights to inform future design and development.